2022
DOI: 10.3390/ani12131725
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Movements and Behavior of Bighead Carps (Hypophthalmichthys nobilis) Considering Fish Passage Energetics in an Experimental Vertical Slot Fishway

Abstract: An understanding of fish movement behavior in response to flow field variables is important for exploring the hydrodynamic strategies of fish in fish passages. In this paper, bighead carps were taken as an example. The fish movement behavior response to water flow field information by means of estimating the energetic expenditure using an IBM approach in an experimental fishway was investigated. Fish swimming velocity, drag force, and energy expenditure were analyzed in varied flow conditions related to hydrau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Moreover, an individual-based model, combined with the Lagrangian and Eulerian frameworks, can illustrate the interaction between the fish behavior and hydrodynamics conditions, which is closely related to the indicator of energy consumption of fish (Goodwin et al, 2006(Goodwin et al, , 2014. The evidence suggests that fishes use more energy while migrating through high turbulent kinetic energy zones, which can reduce passage success since fatigued fish are less likely to cross the zone (Guiny et al, 2005;Liu et al, 2006;Tan et al, 2022) Celestino, et al, 2018;Bunt & Jacobson, 2019;Burnett et al, 2014;Gowans et al, 1999;Lundqvist et al, 2008;Naughton et al, 2007;Steffensen et al, 2013);…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, an individual-based model, combined with the Lagrangian and Eulerian frameworks, can illustrate the interaction between the fish behavior and hydrodynamics conditions, which is closely related to the indicator of energy consumption of fish (Goodwin et al, 2006(Goodwin et al, , 2014. The evidence suggests that fishes use more energy while migrating through high turbulent kinetic energy zones, which can reduce passage success since fatigued fish are less likely to cross the zone (Guiny et al, 2005;Liu et al, 2006;Tan et al, 2022) Celestino, et al, 2018;Bunt & Jacobson, 2019;Burnett et al, 2014;Gowans et al, 1999;Lundqvist et al, 2008;Naughton et al, 2007;Steffensen et al, 2013);…”
Section: Discussionmentioning
confidence: 99%
“…Of particular concern are many migratory freshwater fish species which must reach their spawning‐, rearing‐, and overwinter habitats to complete their normal life cycle (Bao et al, 2019; Sullivan et al, 2019). There are many examples suggesting that the decline or obstruction of their migration routes caused by dams, culverts, or other anthropogenic activities, can impact freshwater biodiversity by directly decreasing the migratory fish populations (Antonio et al, 2007; Bao et al, 2019; Benitez et al, 2022; Frissell, 1993; Hatry et al, 2016; Pasha et al, 2015; Silva et al, 2018; Tan et al, 2022). For example, Chen et al (2022) found various economic migratory species (e.g., Ctenopharyngodon idella , Hypophthalmichthys nobilis , and Mylopharyngodon piceus ) which were historically common in the Pearl River have been rarely identified in the recent survey due to the long‐term obstruction of the Changzhou Dam.…”
Section: Introductionmentioning
confidence: 99%
“…The side walls were made of highly transparent organic glass (with a thickness of 15 mm). The origin of the experimental model coordinates was the starting point of the left board; the X-axis was parallel to the bottom and points downstream with the horizontal slot line, the Y-axis was perpendicular to the bottom, and the Z-axis was transverse [26,27]. The valvular and related structures were made of 3D-printed nylon material, and the test island was made of wood.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Water velocity gradient Dijkgraaf, 1963;Royce et al, 1968;Fausch and White, 1981;Kalmijn, 1988Kalmijn, , 1989Fausch, 1993;Fletcher, 1994;Hayes and Jowett, 1994;McLaughlin and Noakes, 1998;Braun and Coombs, 2000;Crowder and Diplas, 2000;Montgomery et al, 2000;Kemp et al, 2003;Goodwin, 2004;Goodwin et al, 2006;Sweeney et al, 2007;Nestler et al, 2008;Russon and Kemp, 2011;Abdelaziz et al, 2013;Vowles et al, 2014;Oteiza et al, 2017;Albayrak et al, 2020;Beck, 2020;Swanson et al, 2020;Zhu L. et al, 2021;Tan et al, 2022;Li et al, 2023 Turbulence MacKinnon andHoar, 1953;Pavlov et al, 1982;Pavlov and Tyuryukov, 1993;Skorobogatov et al, 1996;Coutant, 1998;Coutant and Whitney, 2000;Crowder and Diplas, 2000;Pavlov et al, 2000;Cada and Odeh, 2001;Coutant, 2001;Crowder and Diplas, 2002;Enders et al, 2003;Smith, 2003;Lupandin, 2005;…”
Section: Fish Behavior Responsementioning
confidence: 99%